Understanding Climate Change Adaptation Issues in Nepal - Dahal, Ngamindra (The Initiation, 2010)
Nepal has observed trend of annual increase in temperature per decade by 0.41°C which is much higher than global average. Climate change is relatively new challenge of global scale but have strong local effects. The evidences of the global warming and climate change are more prominent on the Himalayan region of the globe with melting of ice, glacier retreat, and worst of all the incidence of glacial lake outburst floods with the aftermath falling directly on the ecosystem. The most critical areas are the resource poor developing countries like Nepal which are first to face this calamity yet helpless to implement any concrete ideas still. Nepal has to develop its mechanism to disseminate information regarding climate change and its rational use in planning and implementing policy processes with simultaneous approach on the research to follow the trend of climate change. Thus, this paper focuses on Nepal strategies to cope with challenges of climate change keeping in view the shifting focus of global climate policy. Key Words: Climate change, Global warming, Glacial retreat, Depleting ice, Ecosystem DOI: 10.3126/init.v2i1.2536 The Initiation Vol.2(1) 2008 pp138-144